So you want to earn a Ph. D. in economics : how long do you think it will take? - John J. Siegfried; Wendy A. Stock (Williams College, Williams Project on the Economics of Higher Education (WPEHE), 2000)
The elapsed time taken to earn a Ph.D. in economics is analyzed with data from 620 (of about 950) 1996-97 Ph.D.s. The median is 5.3 years. A duration model indicates that those students at several of the most highly regarded programs, those supported by no-work fellowships, and those holding a prior masters degree finish faster than others. Americans, those who start jobs before completing their degree, and those who have children take longer. Kids slow the progress of women, but not of men. The only difference among fields is a longer time required for industrial organization and international economics. There is no difference in time-to-degree between men and women, married and single students, older and younger students, and those enrolled in larger or smaller Ph.D. programs. Fellowship support is more important for speeding the progress of women than that of men.
Keywords: 330; Wirtschaftswissenschaftler; Gehalt; Berufseinstieg; USA